EMPOWERMENT OF THE COMMUNITY OF PALUH KEMIRI SUB-DISTRICT LUBUK PAKAM IN IMPROVING THE SENSE OF BELONGING TOWARDS CIVIL COMMUNITY - Nur Aisyah; Adelina Lubis (International Journal of Engagement and Empowerment, 2022)
Sense of belonging is the experience of personal involvement in a system or environment so that people feel an integral part of the system or environment. Paluh Kemiri Village, Lubuk Pakam District, has enormous potential to be developed if the existing programs in the government can be followed up jointly by the government, the community and universities. This community service is held with the following objectives: 1) Institutional improvement. 2) Business improvement. 3) Revenue improvement. 4) Environmental improvement. 5) Improvement of life. 6) Community improvement. The community empowerment approach that has been implemented so far is still problem based. Whereas the powerlessness of the community covers all aspects, apart from educational factors, as well as structural and social factors as well as environmental conditions and policies that are not conducive to growing creativity and productivity of micro-economic actors and small and medium-sized enterprises in developing local potential. To advance the potential of the region, it is necessary to have knowledge of technology and innovation as well as creativity towards agropreneurship and technopreneurship. For this reason, a change in the way of thinking and acting as an entrepreneur is needed in increasing the sense of belonging to civil society. Following successful empowerment activities, community empowerment needs to be in line with community service activities